PROBLEMATIKA PELAYANAN KESEHATAN RUMAH SAKIT UMUM DAERAH (RSUD) BENGKALIS KABUPATEN BENGKALIS TAHUN 2011-2013 - Hadi Fuadi; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Health is one of the many fields in contact directly with the public, the public service aspect becomes very important. This is because the Ministry of health should have values of satisfaction measured so that it can become a reference in the improvement of service quality. Health shall provide health services in a fast, precise, friendly and affordable by all the layers so as to provide convenience for the public. But in fact it is often found that when a society experiencing problems in getting the healthcare they need, and this is certainly arise the negative impact to the survival of the community. This is caused by several factors, namely the limited medical personnel, the limited stock of drugs and the infrastructure is not yet adequate. The purpose of this study is to analyze and explain the obstacles in the service of public hospitals (HOSPITALS) of Bengkalis Area in carrying out the tasks and functions as a waiter.Type of this research is a descriptive i.e. researchers provide a description and overview of the phenomenon or social symptoms examined by independent variables described in a systematic and accurate. Method of data collection is done by means of interviews and the documentation.The results of this study showed that the health service HOSPITALS Bengkalis Regency of Bengkalis which was carried out according to its function has not been going well in accordance with the goals and targets that have been set.Keywords:Public Service, Health Service, Hospitals Bengkalis